Partitioning and Server Shadowing for Scheduling Periodic Real-time Tasks on Multiprocessors - Barreto, João; Massa, Ernesto; Lima, George (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2023)
We present the Partitioning and Server Shadowing Algorithm (PSSA for short), designed for scheduling independent periodic tasks with implicit deadlines on multiple identical processors. PSSA carries out one or more steps of partitioning. In the first, tasks are entirely assigned to physical processors. If all tasks are assigned in the first step, PSSA reduces to partitioned EDF. If any task is left unassigned after the first step, PSSA groups unused processor shares via servers to create logical processors in subsequent partitioning steps. When a task is assigned to a logical processor, it is actually assigned to and executes on multiple physical processors and its migration across processors is controlled by an innovative server management scheme, namely server shadowing. Task migration and preemption overheads generated by PSSA were found similar to the best results published to date.